Manajemen Kecerdasan Budaya Dalam Pengembangan Industri di Bidang Pariwisata - Eka Satria Wibawa; Siswanto Siswanto (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2021)
This study explains the concept of intelligence in modern management. In this ever-evolving world technology, companies must be competitive and develop innovatively to face technological globalization. In achieving a high level of competence and competitiveness, companies or organizations need to deepen their cultural and professional knowledge in offering the best products and services and to build loyal relationships to consumers. This study focuses on the role of cultural intelligence in maximizing the effectiveness of supply in various cultural contexts and changing consumption interests. In fact, cultural intelligence provides information about an individual's ability to cope with multicultural situations. Take part in multicultural and cultural, and in culturally diverse working groups. Organizational success in determining management and selecting cultural intelligence will benefit the tourism sector with economic and more competitive advantages. Researchers find ideas in all their complexities into one package that includes the world of culture in the concept, and between cultures as a relational concept.